The Development of Products in the Group of Bathing and Hair Care Products by Increasing the Extract of Fragrant Rice and Marketing Communication to Increase the Value of Products of the Group of Community Enterprises, Large-Scale Rice Farming, Nong Ai Taen, Songkhla Province - Chooset, Noppadon; Saesow, Kulthira; อุทัยหอม ดวงฤดี; Lateh, Likit (Business Administration and Management Journal Review, 2024)
This research aims to 1) Study the current situation and problems of the group of community enterprises 2) Study consumer behavior, marketing mix and consumer purchase intentions 3)Design and develop prototypes of bathing and hair care products and 4)Communicate marketing strategies. This research employs methods of research and development created by a group of 16 community enterprises. Data was collected through group interviews and content analysis. A questionnaire was used to collect data on 400 consumers in Songkhla province, and their characteristics were described using percentages. Quantitatively, behavior, marketing mix, and purchase intentions were analyzed using average values and standard deviations. The study found that the group had leftover fragrant rice from rice dyeing, which was utilized as an ingredient to add value to the products. Consumer behavior analysis revealed that the majority of respondents had a positive perception towards purchasing convenience. In terms of marketing communication, consumer needs and costs were found to be important factors. Consumers’ purchasing intentions were found to be high. This study discovered that fragrant rice was present in three personal care products, namely liquid soap, shampoo, and hair conditioner. These products were found to use integrated marketing communication strategies both online and offline.